Improving Motivation and Learning Outcomes of Elementary School Students with Multimedia-Based Interactive Media - Yonanda, Devi Afriyuni; Islahuddin, Islahuddin; Ramadhani, Fauziah Aulia; Febriyanto, Budi; Saputra, Dudu Suhandi; Yuliati, Yuyu; Nurhidayat, Eka (Profesi Pendidikan Dasar, 2024)
This study addresses challenges in 21st-century education, particularly the low motivation and academic performance of elementary school students. It investigates the use of multimedia-based interactive learning tools as a solution to improve engagement and learning outcomes. Focusing on the Hydrological Cycle (Theme 8) for fifth-grade students, the research aimed to develop interactive multimedia learning materials using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through questionnaires, interviews, and assessments, then analyzed using quantitative and qualitative descriptive methods. The findings revealed strong validity, practicality, and effectiveness of the developed materials. Material and media experts rated the tool’s validity at 90%, classifying it as highly valid. Practicality tests yielded scores of 98.3% from teachers and 86.9% from students, confirming its usability in classroom settings. Most notably, the tool significantly improved learning outcomes, with average test scores rising from 48.79 (pretest) to 81.47 (post-test). These results demonstrate that interactive multimedia tools can effectively enhance student motivation and academic achievement in elementary education